Comparison of Different Recovery Strategies After High-Intensity Functional Training: A Crossover Randomized Controlled Trial - Martínez-Gómez, Rafael; Valenzuela, Pedro L.; Lucia, Alejandro; Barranco-Gil, David (Frontiers in Physiology, 2022)
We aimed to determine whether voluntary exercise or surface neuromuscular electrical stimulation (NMES) could enhance recovery after a high-intensity functional training (HIFT) session compared with total rest. The study followed a crossover design. Fifteen male recreational CrossFit athletes (29 ± 8 years) performed a HIFT session and were randomized to recover for 15 min with either low-intensity leg pedaling (“Exercise”), NMES to the lower limbs (“NMES”), or total rest (“Control”). Perceptual [rating of perceived exertion (RPE) and delayed-onset muscle soreness (DOMS) of the lower-limb muscles], physiological (heart rate, blood lactate and muscle oxygen saturation) and performance (jump ability) indicators of recovery were assessed at baseline and at different time points during recovery up to 24 h post-exercise. A significant interaction effect was found for RPE (p = 0.035), and although post hoc analyses revealed no significant differences across conditions, there was a quasi-significant (p = 0.061) trend toward a lower RPE with NMES compared with Control immediately after the 15-min recovery. No significant interaction effect was found for the remainder of outcomes (all p > 0.05). Except for a trend toward an improved perceived recovery with NMES compared with Control, low-intensity exercise, NMES, and total rest seem to promote a comparable recovery after a HIFT session.